2013
DOI: 10.1371/journal.pone.0058690
|View full text |Cite
|
Sign up to set email alerts
|

Population-Based Study of Birth Prevalence and Factors Associated with Cleft Lip and/or Palate in Taiwan 2002–2009

Abstract: BackgroundFacial cleft deformities, including cleft lip with or without cleft palate (CL/P) and cleft palate (CP), are common congenital birth anomalies, especially in Asia. This study aimed to analyze the prevalence of CL/P and CP and to identify associated factors in Taiwan.MethodsThis population-based epidemiological study retrospectively analyzed birth data obtained from the Department of Health in Taiwan for years 2002–2009. Frequency distribution, percentages and related predictors were investigated, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 18 publications
4
34
0
2
Order By: Relevance
“…The present findings revealed a significantly lower birthweight of infants with CPO as compared to the control groups. The same trend has been described in populations in Iran, Taiwan and Uganda …”
Section: Discussionsupporting
confidence: 83%
“…The present findings revealed a significantly lower birthweight of infants with CPO as compared to the control groups. The same trend has been described in populations in Iran, Taiwan and Uganda …”
Section: Discussionsupporting
confidence: 83%
“…The incidence of the anomaly worldwide is 0.3 to 1.9 per thousand live births [13], and the average incidence is 0.8 per thousand live births [1]. China is one of the countries with a high incidence of NSCL/P, at 1.3 per thousand live births [4], which is higher than the world’s average level.…”
Section: Introductionmentioning
confidence: 99%
“…In England, the incidence of clefts is 1.42/1,000 infants . A recent study in Taiwan found a birth rate of 3.2/1,000 facial cleft deformities in newborns . The overall incidence of clefts in Finland is 2.56/1,000 live births and abortions.…”
mentioning
confidence: 99%